Pengaruh Asset Growth, Leverage, dan Dividend Payout Ratio pada Volatilitas Harga Saham - Artikanaya, I Kadek Rama; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 30 No 5 (2020), 2020)
This study aims to obtain empirical evidence about the effect of asset growth, leverage, and dividend payout ratio on stock price volatility. This research was conducted on companies listed in the LQ 45 index on the Indonesia Stock Exchange in 2014 - 2018. The number of samples used was 13 companies using the nonprobability sampling method with a purposive sampling technique, so the number of samples for 5 years became 65 samples. The data analysis technique used is multiple linear regression analysis. Based on the results of the analysis found that asset growth has a negative effect on stock price volatility. Leverage has a positive effect on stock price volatility. Dividend payout ratio has a negative effect on stock price volatility. Keywords: Asset Growth; Leverage; Dividend; Volatility.